Ángel Anguiano promoter of the specialized library of the National Astronomical Observatory of Tacubaya - Zueck, Silvia (Revista General de Información y Documentación, 2017)
This work focuses on the actions carried out by the director of the specialized library of the National Astronomical Observatory of Chapultepec (later in Tacubaya), the civil engineer Ángel Anguiano during the last third of the 19th century, coinciding with the first Porfirian epoch. Based on the detailed review of the primary archival sources that combined the historical and sociological approach, we find that according to the Weberian concept of bureaucracy, a scientific administration was applied in the library with an emphasis on strict rules, which all related to her had to carry out; from this place, promoted the new astronomical observatory and through modern standardized protocols, acquired and select national and international collection of works specialized in practical and theoretical astronomy. The result of this strategy, allowed the users to be updated, to exchange knowledge and to be part of the knowledge society related to astronomy that has lasted until today.